Initiation of Nursing Service Development in the Outpatient Department Using Kotter's Change Theory - Hulu, Soni Roy Kurniawan; Handiyani, Hanny; Pujasari, Hening; Masfuri, Masfuri (Universitas Aisyah Pringsewu, 2023)
Outpatient nursing services are an important element for hospitals to produce many patients, particularly inpatients. Outpatient nursing services are currently still not optimal. Nurses are responsible for providing good service to increase patient satisfaction. Aim: This case report aims to describe the implementation of planned changes to optimize the outpatient nursing service planning function. Method: The method used is a case report. Data collection uses interviews, questionnaires, and field observations. The results of data exploration are then analyzed using SWOT (strengths, weaknesses, opportunities, threats) and fishbone diagrams, then formulating a plan of action (PoA), followed by implementation and evaluation. Results: The results of the study showed that the priority problem in nursing services was that the implementation of the planning function was not optimal. Making outpatient nursing service guidelines is a strategy for solving problems in developing outpatient nursing services. Implementation of problem-solving uses a theory of change approach by the stages of Kotter's eight-step plan. Recommendation: Kotter's eight-step plan theory of change approach can be continued by hospital management as a form of initiation of service development.